Odpowiedź :
⅗x+½y=2
½(2x-y)=2
0,6x+0,5y=2 /*10
0,5(2x-y)=2
6x+5y=20
x-0,5y=2 /*10
6x+5y=20
10x-5y=20
16x=40
x = 2,5
6*2,5 +5y=20
15+5y=20
y=1
½(2x-y)=2
0,6x+0,5y=2 /*10
0,5(2x-y)=2
6x+5y=20
x-0,5y=2 /*10
6x+5y=20
10x-5y=20
16x=40
x = 2,5
6*2,5 +5y=20
15+5y=20
y=1
3/5x+1/2y=2/*10
1/2(2x-y)=2
6x+5y=20
x-1/2y=2/*2
6x+5y=20
2x-y=4
6x+5y=20
-y=4-2x/(-1)
6x+5y=20
y=-4+2x
6x+5*(-4+2x)=20
y=-4+2x
6x-20+10x=20
y=-4+2x
16x=40/16
y=-4+2x
x=2,5
y=-4+2*2,5
x=2,5
y=1
1/2(2x-y)=2
6x+5y=20
x-1/2y=2/*2
6x+5y=20
2x-y=4
6x+5y=20
-y=4-2x/(-1)
6x+5y=20
y=-4+2x
6x+5*(-4+2x)=20
y=-4+2x
6x-20+10x=20
y=-4+2x
16x=40/16
y=-4+2x
x=2,5
y=-4+2*2,5
x=2,5
y=1